Fostering changes in attitude, knowledge and behavior: demographic variation in environmental education effects. Issue 6 (3rd June 2018) - Braun, Tina; Cottrell, Richard; Dierkes, Paul
Abstract: This study employs a uniquely multi-factorial, large-scale design to investigate baseline differences and the effects of a singular outdoor educational program on environmental attitudes, knowledge and behavior among primary and secondary school students educated in four different countries. Statistical modelling approaches employed country of residence, age, nationality, sampling year, gender and urban/ rural habitation as predictor variables. Baseline scores were explained by a number of predictors but country of residence and rural-urban differences appeared as the most consistent explanatory variable for positive changes in attitude, knowledge and behavior. Given the nexus of political, social, natural and cultural data contained within the residence variable, we discuss the complex web of drivers that may influence environmental literacy and environmentally responsible behavior. Spatial variation in the value of outdoor education programs is also discussed.